The emperor's new dystrophin: finding sense in the noise. Issue 7 (July 2015) - Wilton, S.D.; Veedu, R.N.; Fletcher, S.
Highlights: Dystrophin restoring therapy should increase dystrophin expression after treatment. Restoration of functional dystrophin will take months to result in clinical benefit. Eteplirsen-treated DMD boys show slower disease progression than predicted from the natural history. Abstract : Targeted dystrophin exon removal is a promising therapy for Duchenne muscular dystrophy (DMD); however, dystrophin expression in some reports is not supported by the associated data. As in the account of 'The Emperor's New Clothes', the validity of such claims must be questioned, with critical re-evaluation of available data. Is it appropriate to report clinical benefit and induction of dystrophin as dose dependent when the baseline is unclear? The inability to induce meaningful levels of dystrophin does not mean that dystrophin expression as an end point is irrelevant, nor that induced exon skipping as a strategy is flawed, but demands that drug safety and efficacy, and study parameters be addressed, rather than questioning the strategy or the validity of dystrophin as a biomarker.